Microbiological quality of water from hand-dug wells used for domestic purposes in urban communities in Kumasi, Ghana - Akple, Maxwell Selase Kwasi; Keraita, Bernard N.; Konradsen, Flemming; Agbenowu, E. (Informa UK Limited, 2011)
Assessment was done on the microbiological quality of water in hand-dug wells in urban communities in Kumasi, Ghana. A total of 256 water samples were taken from eight wells and examined for faecal coliforms, enterococci and helminths. High contamination levels were recorded in the wells, more so in the wet season, with faecal coliforms levels between 6.44 and 10.19 log units and faecal enterococci between 4.23 and 4.85 CFU per 100 ml. Influence on protection and lining of wells on water quality was not pronounced but mechanization reduced contamination significantly by about 3 log units. This study shows a stronger influence of poor sanitation and improper placement of wells on water quality compared to improvements made from lining and protection of wells. In the race to increase access to drinking water in poor urban settlements, quality of groundwater could be a major barrier, if provision of drinking water is not matched with improvements in sanitation and urban planning.